Wireless motion sensor light for home zone security - Khairul Anwar, Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Wireless sensor network is now gaining attention in technology field as it has great potential to improving human life and useful in many application such as smart home, monitoring, surveillances and personal care. Furthermore, with the increasing of installation and maintenance cost of the system where used the traditional wired link network, the wireless is the preferred choice as it reduce the maintenance cost and give greater scalability. Due to existing of the wireless sensor network, house security system become one of the best solution to overcome the intrusion problem but many types of house security system are too expensive and hard to be used so the system based on the WSN can be resolve where user can program the security system by their own. In this thesis, it focuses on developing a house security system based on WSN and Passive Infrared motion detector which controlled by the Arduino microprocessor. The overall project is divided into 2 part. The first part consist of the hardware for the transmitter and the receiver which are the PIR sensor, LDR sensor and RF transmitter which connected to the Arduino board for transmitter part. The Relay, LED for first receiver part and the buzzer and display at the second receiver part. The second part, is on the software programming to operate the hardware structure and is based on the C programming language. This system is simple to used and is proposed for detect the human motion and provide the information to the user and it will alert the user inside their house and at the same time the precaution measure can be take.